An Actuator Fault Detection and Isolation method design for Planar Vertical Take-off and Landing Unmanned Aerial Vehicle modelled as a qLPV system*. Issue 5 (2016) - Ortiz-Torres, G.; López-Estrada, F.R.; Reyes-Reyes, J.; García-Beltrán, C.D.; Theilliol, D.
Abstract: This paper presents the design of a tracking controller and a fault detection and isolation system for a Planar Vertical Take-off and Landing (PVTOL) Unmanned Aerial Vehicle (UAV) under actuator faults. In order to control the PVTOL, the dynamic system is divided into three subsystems driven by the rotational, the altitude, and the position dynamics. The altitude and position subsystems are based on qLPV model while the rotational subsystem is linear. A linear observer applied to the rotational subsystem is considered to detect actuator faults, which can occur as failures (loss of a propeller or a motor) or partial faults (degradation). Furthermore, fault isolation is done by measuring roll velocity due to the actuator fault. In all cases, sufficient conditions for the existence of the observer and the controllers are given in terms of linear matrix inequalities (LMIs). Finally, simulations (on the nonlinear model) are done in order to illustrate the effectiveness of the proposed methodology.